Intermittent rises in plasma homocysteine in patients with rheumatoid arthritis treated with higher dose methotrexate. Issue 1 (17th December 2004) - Hoekstra, M; Haagsma, C J; Doelman, C J A; van de Laar, M A F J
Abstract : Objectives: To investigate the effect of higher weekly maintenance dose methotrexate (MTX) (⩾25 mg/week) on plasma homocysteine concentrations in adults with RA. Methods: Patients with RA were treated with high doses of MTX with adjuvant folic acid. Plasma homocysteine was determined at baseline and 1, 2, 4, 8, 12, and 48 hours after subcutaneous MTX administration. Maximum homocysteine concentrations after MTX administration were compared with baseline concentrations. Results: Fifteen patients with RA (11 women) were included, with a median age of 61 years (range 31–72) and median disease duration 7 years (range 2–32). Median MTX dose was 30 mg (range 25–40). All patients received folic acid supplementation (5–30 mg/week). Median plasma homocysteine concentration at baseline was 10.1 μmol/l (range 6.6–12.7; normal 6–15). Homocysteine concentrations increased after MTX administration by a median of 2.5 μmol/l (range 0.7–5.1). Median maximum plasma homocysteine was significantly higher than at baseline. Peak homocysteine was reached after 12 hours. No relation between serum folate concentrations and plasma homocysteine concentrations was found. Conclusions: In patients with RA higher MTX doses with adjuvant folic acid do not increase baseline concentrations of homocysteine. An intermittent significant rise in plasma homocysteine occurs in the 48 hours after MTX administration.